(untitled) (Edad Media. Revista de Historia, 2020)
As medieval centuries drew on, Christian authorities were increasing their pressure on the religious minorities of their realms. At the dawn of the Modern Ages, the tolerance towards those minorities had virtually disappeared and their condition was more and more uncertain. However, despite their condition of dominated minority, the Mudejar community showed signs of sufficent cohesion and solidarity to oppose directly some of those resolutions agaist their interest. even if they were not abolished, the Mudejar managed to postpone and moderate them, due to their rebellious attitude.